Analysis of antigenicity of Clostridium botulinum type C1 and D toxins by polyclonal and monoclonal antibodies. - Oguma, K (1984)
Clostridium botulinum type C1 toxin was purified from C-Stockholm (C-ST), and D toxin was purified from D-1873 and D-South African. Polyclonal antibodies against these toxins were prepared in rabbits. Twenty-eight monoclonal antibodies to these toxins were also prepared with BALB/c myeloma cells. The antibodies were analyzed by both enzyme-linked immunosorbent assay (ELISA) and a toxin neutralization test. ELISA was performed with the three purified toxins and heavy-chain (Hc) and light-chain (Lc) components derived from C-ST and D-1873 toxins. A neutralization test was carried out with 11 toxin preparations (7 from type C and 4 from type D cultures). ELISA results indicated that there exists at least one common antigenic determinant on each of the Hc and Lc components of the three purified toxins. The results of the neutralization test also indicated that type C1 and D toxin preparations contain several common antigenic sites in their molecules. Some are common to toxins from several specific cultures, whereas others are common to toxins from a large number of cultures. It was speculated that toxins from two type C strains are composed of Hc and Lc components which are somewhat similar to those of D-1873 and C-ST toxins, respectively.